A comparison of chemical composition, bioactive components and hypoglycemic activity of Stigma maydis obtained from different growing times - Yi Zhang; Jinxin Pang; Lianmou Yao; Chunfang Wang; Bingjie Chen; Qi Zheng; Yingxiong Hu; Yongjin Qiao (Cogent Food & Agriculture)
Stigma maydis (SM) possesses remarkable nutritional value due to the presence of health-protective chemical constituents in it. Despite its commercial uses, there is a lack of information on changes in the nutritional profile of SM during Shenke 601 waxy corn development by following four different maturity stages (silking stage; blister stage; milky stage; dough stage). In this study, the ideal times for the development of seven active compounds (polysaccharides, saponin, rutin, luteolin, quercetin, kaempferol and chlorogenic acid) were at the silking stage. The total flavonoid and total phenol content increased as the SM matured. Except for the above-mentioned active compounds, the content of major nutritional components of dough stage was higher than that of three other stages. The extract of Stigma maydis exhibited good α-amylase, α-glucosidase and pancreatic lipase inhibition activities. The ethanolic SM extracts showed better inhibitory effects than aqueous SM extracts with a dose–effect relationship. The hypoglycemic activity of ethanolic extract was higher than that of aqueous extract at each stage. This provided an important basis for the application of SM.